Metastatic Cervical Cancer Presenting as a Sessile Polyp in the Ascending Colon - Loho, Imelda Maria; Siregar, Lianda; Iriani, Dewi; Faatinah, Tiyas Hasnaa (The Indonesian Society for Digestive Endoscopy, 2024)
Patients with metastatic cervical cancer, particularly hematogenous metastasis, have a worse prognosis compared to those with localized cervical cancer. Gastrointestinal involvement of cervical cancer occurs in approximately 8% of cases and most lesions are located in the recto-sigmoid area due to direct extension of the disease. Here, we present a case of cervical adenocarcinoma spreading to the ascending colon as a sessile polyp and mimicking a hyperplastic polyp. Histopathological evaluation followed by immunohistochemistry analysis is needed to confirm the diagnosis.